Using 67Cu to Study the Biogeochemical Cycling of Copper in the Northeast Subarctic Pacific Ocean - Semeniuk, David M.; Bundy, Randelle M.; Posacka, Anna M.; Robert, Marie; Barbeau, Katherine A.; Maldonado, Maria T. (Frontiers in Marine Science, 2016)
Microbial copper (Cu) nutrition and dissolved Cu speciation were surveyed along Line P, a coastal to open ocean transect that extends from the coast of British Columbia, Canada, to the high-nutrient-low-chlorophyll (HNLC) zone of the northeast subarctic Pacific Ocean. Steady-state size fractionated Cu uptake rates and Cu:C assimilation ratios were determined at in situ Cu concentrations and speciation using a 67Cu tracer method. The cellular Cu:C ratios that we measured (~30 μmol Cu mol C−1) are similar to recent estimates using synchrotron x-ray fluorescence (SXRF), suggesting that the 67Cu method can determine in situ metabolic Cu demands. We examined how environmental changes along the Line P transect influenced Cu metabolism in the sub-microplankton community. Cellular Cu:C assimilation ratios and uptake rates were compared with net primary productivity, bacterial abundance and productivity, total dissolved Cu, Cu speciation, and a suite of other chemical and biological parameters. Total dissolved Cu concentrations ([Cu]d) were within a narrow range (1.5–2.8 nM), and Cu was bound to a ~5-fold excess of strong ligands with conditional stability constants (KCuL,Cu2+cond) of ~1014. Free Cu2+ concentrations were low (pCu 14.4–15.1), and total and size fractionated net primary productivity (NPPV; μg C L−1 d−1) were negatively correlated with inorganic Cu concentrations ([Cu′]). We suggest this is due to greater Cu′ drawdown by faster growing phytoplankton populations. Using the relationship between [Cu′] drawdown and NPPV, we calculated a regional photosynthetic Cu:C drawdown export ratio between 1.5 and 15 μmol Cu mol C−1, and a mixed layer residence time (2.5–8 years) that is similar to other independent estimates (2–12 years). Total particulate Cu uptake rates were between 22 and 125 times faster than estimates of Cu export; this is possibly mediated by rapid cellular Cu uptake and efflux by phytoplankton and bacteria or the effects of grazers and bacterial remineralization on dissolved Cu. These results provide a more detailed understanding of the interactions between Cu speciation and microorganisms in seawater, and suggest that marine phytoplankton modify Cu speciation in the open ocean.